Studi In Silico Potensi Metabolit Sekunder Eleutherine palmifolia (L.) Merr. sebagai Inhibitor Protein E6 dan E7 dari Human Papilloma Virus - Dinda Fluor Agustin; Mariana Wahjudi (Keluwih: Jurnal Kesehatan dan Kedokteran, 2022)
Abstract—Human Papilloma Virus (HPV), especially variants 16 and 18, are the causative agents of cervicals cancer. The E6 and E7 proteins are known to play a role in the cervical cancer regulation. Dayak onion plants have been widely used by local people as traditional medicine, including in treating cancer. Until now, there is no known compound or scientific evidence related to its activity of Dayak onion plants against HPV. The plant contains flavonoids, alkaloids, naphtoquinone and several types of polyphenols. Several flavonoids and naphtoquinones from other plants are known to have the ability to treat cancer, especially cervical cancer. In this study, we performed in silico screening of the secondary metabolites, especially the flavonoid and naphtoquinone groups, of Dayak onions which might be active against E6 and E7 proteins of HPV16 and 18. The result showed that there were six flavonoids’ compounds and four naphtoquinone compounds which were predicted as candidates to treat cervical cancer. The Pa values of all compounds, including the positive control, the resveratrol, were less than 0.5 which meant that all compounds showed no activity as anticancer. Analysis of physicochemical, pharmacokinetics, and toxicity predictions exhibited that all compounds could be absorbed, distributed, metabolized, and excreted in human body and non-toxic. Among the ten compounds, only 1,4-Naphthoquinone had weaker interaction with E6 and E7 proteins than resveratrol. Ephicatecin gallate had the strongest binding affinity with protein E6 HPV16 (-7,7 kkal.mol-1) and E7 HPV18 (-7,1 kkal.mol-1), whilst rutin was the strongest interaction with E6 HPV16 (-7,8 kkal.mol-1) and E7 HPV18 (-6,2 kkal.mol-1). As a conclusion, the ephicatecin gallate and rutin compounds of BDayak onion could be used as potent candidat to inactivate the E6 and E7 proteins of HPV 16 and HPV18. The two compounds were also predicted had similarity as medicine and were suitable in bioavailability to be applied as agents for cervical cancer therapy. Keywords: E6 and E7 oncogene proteins, cervical cancer, flavonoid, naphtoquinone, onion dayak Abstrak—Human Papiloma Virus (HPV) varian tipe 16 dan 18 merupakan salah satu penyebab kanker serviks. Protein E6 dan E7 dari HPV merupakan protein utama yang berperan dalam regulasi kanker servix. Tanaman Bawang Dayak telah banyak digunakan secara tradisional untuk mengatasi kanker. Hingga saat ini belum diketahui senyawa atau pembuktian ilmiah terkait khasiatnya pada tanaman Bawang Dayak. Bawang Dayak mengandung senyawa flavonoid, alkaloid, naphtoquinone dan beberapa tipe polifenol. Beberapa senyawa golongan flavonoid dan naphtoquinone dari tumbuhan lain telah dibuktikan berperan dalam mengatasi kanker, terutama kanker servix. Pada penelitian ini dilakukan skrining secara in silico metabolit sekunder, khususnya golongan flavonoid dan naphtoquinone, dari Bawang Dayak yang berpotensi menghambat protein E6 dan E7 dari HPV16 dan HPV18. Hasil analisis menunjukkan bahwa ada enam senyawa golongan flavonoid dan dan empat senyawa naphtoquinone yang diduga berpotensi sebagai anti kanker serviks. Nilai Pa kurang dari 0,5 untuk semua metabolit sekunder dan kontrol positif, resveratrol tidak menunjukkan aktivitas. Analisis sifat fisikokimia, farmakokinetik dan potensi toksisitas bagi tubuh menunjukkan bahwa semua senyawa teridentifikasi mampu diabsorbsi, didistribusi, dimetabolisme dan diekskresi dari tubuh dan tidak toksik. Interaksi sepuluh metabolit sekunder Bawang Dayak dengan protein E618 dan E716 menunjukkan bahwa hanya 1,4-Naphthoquinone yang berinteraksi lebih lemah dibandingkan resveratrol. Ephicatecin gallate berinteraksi paling kuat dengan protein E6 HPV16 (-7,7 kkal.mol-1) dan E7 HPV18 (-7,1 kkal.mol-1). Rutin berinteraksi paling baik dengan E6 HPV16 (-7,8 kkal.mol-1) dan E7 HPV18 (-6,2 kkal.mol-1). Berdasarkan hasil analisa, dapat disimpulkan bahwa senyawa ephicatecin gallate dan rutin Bawang Dayak berpotensi sebagai kandidat penghambat protein E6 dan E7 dari HPV 16 dan HPV18. Kedua senyawa juga diduga memiliki kesamaan dengan obat dan secara bioavailibilitasnya cocok jika diterapkan sebagai agen terapi kanker serviks. Kata kunci: bawang dayak, flavonoid, kanker servix, naphtoquinone, protein onkogen E6 dan E7